Magnetic susceptibility zonation of the melilititic Riedheim dyke (Hegau volcanic field, Germany): evidence for multiple magma pulses? - Wall, Helga de; Kontny, Agnes; Vahle, Carsten (Journal of volcanology and geothermal research, 2004)
The olivine-melilitic Riedheim dyke complex is related to the Tertiary alkaline magmatism within the Hegau volcanic field. Magnetic susceptibility measurements and the mineral composition of oxides together with petrographic observations imply two phases of magma intrusion for the emplacement of this dyke. The first intrusion forms the eastern and western margins of the dyke section with high magnetic susceptibility values of up to 75×10−3 SI which are related to ferrimagnetic Mg-Al(-Cr)-bearing titanomagnetites with a magnetite component between 0.59 and 0.75 mol%. A generally lower magnetic susceptibility of up to 45×10−3 SI and a significantly lower and homogeneous magnetite component of the titanomagnetites (XMt=0.38 mol%) are recorded for the second intrusion into the central part of the dyke. Furthermore, a dependence of magnetic susceptibility on the amplitude of the ac-field was measured, which is more pronounced in the second intrusion (χHd=25%) than in the first one (6%<χHd<10%) confirming the magneto-mineralogical data. Secondary pervasive alteration is more pronounced in the first intrusion phase, characterised by a very fine-grained and glassy matrix that is more receptive to hydrothermal overprint than the well crystallised matrix of the second intrusion. Localised, thermally induced alteration at the intimately fractured contact between the first and second intrusion phase has oxidised the titanomagnetite of the first intrusion phase but did not significantly effect the second intrusion. Differences between the dyke sections are also documented by the anisotropy of magnetic susceptibility (AMS), which reflects a magmatic flow fabric with long axis of the AMS-ellipsoids (magnetic lineation) parallel to the flow direction and short axis normal to the N-S trending dyke boundary. The orientation of the magnetic fabric for the individual magma pulses is different, with a more moderate plunge of the magnetic lineation within both the western (177°/57°) and eastern parts (181°/50°) of the first dyke intrusion compared to a nearly vertical orientation in the second, central dyke intrusion (180°/78°). We suggest that the primary crystallisation history of the two intrusion phases caused the magnetic susceptibility zonation in the Riedheim dyke complex.
Available online 24 December 2003
Gesehen am 24.09.2020